P-wave beat-to-beat analysis to predict atrial fibrillation recurrence after catheter ablation. (3rd October 2022) - Tachmatzidis, D; Mouselimis, D; Tsarouchas, A; Filos, D; Antoniadis, A P; Lysitsas, D N; Mezilis, N; Sakellaropoulou, A; Giannopoulos, G; Bakogiannis, C; Triantafyllou, K; Fragakis, N; et al.
Abstract: Introduction: Identification of patients prone to atrial fibrillation (AF) relapse after catheter ablation is essential for better patient selection and risk stratification. Purpose: The current prospective cohort study aims to validate a novel P-wave index based on beat-to-beat (B2B) P-wave morphological and wavelet analysis designed to detect patients with low burden AF, as a predictor of AF recurrence within a year after successful catheter ablation. Methods: 12-lead ECG and 10-minute vectorcardiogram (VCG) recordings were obtained from 138 consecutive patients scheduled for AF ablation. Pre-ablation B2B P-wave index, along with standard P-wave indices, clinical scores and patients history and physical examination parameters were evaluated as AF recurrence predictors. Results: Univariate analysis revealed that patients with higher B2B P-wave index had a two-fold risk for AF recurrence (HR: 2.35, 95% CI: 1.24–4.44, p: 0.010). Prolonged P-wave, interatrial block, early AF recurrence, female gender, heart failure history, previous stroke, and CHA2DS2-VASc score ≥2 were also found to be related to higher recurrence rate. Multivariate analysis of predictors that can be assessed before ablation revealed that B2B P-wave index, along with heart failure history and history of previous stroke or transient ischemic attack are independent predicting factors of AF relapse. Conclusion: B2B P-wave morphology and wavelet analysis, is a promising, non-invasive technique, able to identify patients prone to AF recurrence after pulmonary veins ablation. Further studies are needed to assess the predictive value of B2B index with greater accuracy and evaluate a possible relationship with atrial substrate analysis. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Hellenic Society of Cardiology